Discussion of “Managers' Discretionary Adjustments: The Influence of Uncontrollable Events and Compensation Interdependence” - van Rinsum, Marcel (Contemporary Accounting Research, 2015)
Abstract In this discussion of Bol, Hecht and Smith (this issue; BHS), I examine their theory and experimental setting with the purposes of investigating how their study generalizes and identifying further research possibilities. First, I discuss the uncontrollable events the study addresses, which are influenceable and require innovative effort to prevent adverse effects. What follows next is an analysis of experimental design choices and their implications. In particular, results could be specific to the manipulation of event likelihood, as well as to the properties of the objective bonus system and form of subjectivity. This illustrates how evaluation system design properties can create diverse reference points and affect perceived fairness and discretionary adjustments. Together, these points indicate wherein the contribution of BHS lies, and provide an outline for future research opportunities by suggesting alternative research choices.